Evaluation and Influencing Factors of Urban Blue-Green Space Publicness in Changsha - Zhang Chen; Zhang Nan; Zhu Peijuan; Qin Shuqian; Zhang Yong (Redai dili)
Urban Blue-Green Spaces (UBGS) are material carriers that support public life and expand social interactions. It is also a natural place to realize the spatial publicness. In the context of the ecological civilization, China has made specific achievements in constructing a UBGS. However, optimizing its spatial structure and improving the quality of the human environment is only the beginning. Enhancing its publicness and thus strengthening social cohesion, enriching cultural diversity, cultivating the public spirit, and realizing the well-being of humankind on a broader scale is the ultimate goal of UBGS. Drawing on the theories of the human-land relationship and landscape ecology, we established an evaluation system for UBGS publicness based on the "element-function-structure" framework. We used Changsha as an example to explore the UBGS publicness pattern characteristics and influencing factors. The study results are as follows: 1) A UBGS with high publicness should have three significant characteristics: accessible elements, selectable functions, and shared structures, which promote and expand public life and support other social connections. 2) The comprehensive indicator of UBGS publicness in Changsha showed a circular pattern, decreasing from the core to the periphery and a fan-shaped expansion relying on the water system. Regarding element accessibility, spatial accessibility was high in the core area and low in the suburbs. In contrast, quantity adequacy was low in the core area and high in the suburbs. In terms of functional selectivity, group inclusiveness was low along the Xiangjiang River in the core and center areas and lower on the east bank than on the west bank, whereas functional diversity was high in the core area and low in the suburban areas. In terms of structural connectivity and shareability, interactive connectivity shows a high core area, a low peri-urban area, and a wedge-shaped interlocking circle pattern in the transition zone between the core area and the peri-urban area, accompanied by a high belt characteristic along the scenic belt; the landscape connectivity shows a low core area, a high peri-urban area, and a pattern characteristic of the west bank of the Xiangjiang River that is higher than that of the east bank. 3) Social demand, economic boosts, and environmental support promote the spatial heterogeneity of the UBGS publicness. Based on the research results, improving the publicness of the UBGS in Changsha can be approached from the following aspects: first, increasing funding and policy support for the construction of the UBGS, expanding its scale, and improving its quality. Second, respecting the spatial distribution characteristics and activity patterns of the public and optimize the functional organization of the UBGS and the surrounding environment. Third, when constructing urban ecosystems, road systems, greenway systems, and public service facility systems, the construction of the UBGS should be considered comprehensively, and the coupling relationship between the UBGS and other urban subsystems should be enhanced. This study constructed a theoretical framework and evaluation system for assessing UBGS publicness and evaluated UBGS publicness on an urban scale. The results of this evaluation will promote the construction of livable cities and the implementation of the concept of sustainable urban development.